Cost-benefit management of intentional domino effects in chemical industrial areas - Chen, Chao; Reniers, Genserik; Khakzad, Nima (Process safety and environmental protection, 2020)
Chemical industrial areas comprising various hazardous installations may be attacked by adversaries, triggering possible intentional domino effects. Compared with accidental domino effects, intentional domino effects may be more difficult to prevent since intelligent and strategic adversaries can adapt their tactics according to protection measures. However, how and to what extent domino effects affect security management is ignored in previous studies. This study proposes a methodology to prevent and mitigate intentional domino effects taking into consideration economic issues in the decision-making process on safety and security resources. The methodology is divided into five parts: threat analysis, vulnerability analysis of installations with respect to intentional attacks, vulnerability analysis of installations subject to possible domino effects caused by the attacks, cost-benefit analysis, and optimization. Net present value of benefits (NPVB) is employed and quantified in the cost-benefit analysis to determine whether a protection strategy (a combination of safety and security measures) is profitable, or not. Besides, an optimization algorithm called “PROTOPT” based on “maximin” strategy is developed to achieve the most profitable protection strategy. An illustrated case study shows that domino effects can not be ignored in security management since they may have a profound impact on adversaries’ strategies.